A phase 3 study to assess the immunogenicity, safety, and tolerability of MenB-FHbp administered as a 2-dose schedule in adolescents and young adults. Issue 2 (21st January 2022) - Drazan, Daniel; Czajka, Hanna; Maguire, Jason D.; Pregaldien, Jean-Louis; Maansson, Roger; O'Neill, Robert; Anderson, Annaliesa S; Balmer, Paul; Beeslaar, Johannes; Perez, John L
Highlights: The MenB-FHbp vaccine is given on a 2-dose (0, 6 mo) or 3-dose (0, 1–2, 6 mo) series. Immunogenicity and safety of the 2-dose series in a phase 3 study are reported. MenB-FHbp administered at 0, 6 mo was well tolerated. Protective bactericidal antibody responses against diverse MenB strains were observed. These findings support the continued use of MenB-FHbp on a 2-dose schedule. Abstract: Background: The MenB-FHbp vaccine is licensed to prevent meningococcal serogroup B disease on either a 2-dose (0, 6 months) or 3-dose (0, 1–2, 6 months) series. This phase 3 study further assessed the immunogenicity and safety of the 2-dose MenB-FHbp schedule. Methods: Subjects 10–25 years of age received MenB-FHbp (months 0, 6) and the quadrivalent meningococcal conjugate vaccine MenACWY-CRM (month 0). Primary immunogenicity endpoints included percentages of subjects achieving ≥ 4-fold increases from baseline in serum bactericidal antibody using human complement (hSBA) titers for 4 diverse, vaccine-heterologous primary serogroup B test strains and titers ≥ lower limit of quantitation (LLOQ; 1:8 or 1:16) for all 4 primary strains combined (composite response) after dose 2; a titer ≥ 1:4 is the accepted correlate of protection. Percentages of participants with hSBA titers ≥ LLOQ for 10 additional vaccine-heterologous strains were also assessed; positive predictive values of primary strain responses for secondary strain responses were determined. Safety was assessed. Results: Overall, 1057 subjects received dose 1 and 946 received dose 2 of MenB-FHbp. Percentages of participants achieving ≥ 4-fold increases in hSBA titers against each primary strain after dose 2 ranged from 67.4% to 95.0% and the composite response was 74.3%. Primary strain responses were highly predictive of secondary strain responses. Most reactogenicity events were mild-to-moderate in severity and did not lead to withdrawal from the study. Adverse events (AEs) considered by the investigator to be related to vaccination occurred in 4.2% (44/1057) of subjects, and there were no serious AEs or newly diagnosed chronic medical conditions considered related to vaccination. Conclusions: MenB-FHbp administered at 0, 6 months was well tolerated and induced protective bactericidal antibody responses against diverse serogroup B strains. Findings provide further support for the continued use of MenB-FHbp on a 2-dose schedule in this population.